About the accuracy of analysis of linear parametric circuits performed by frequency- symbolic method - Shapovalov, Yu.; Mankowsky, S. (Видавництво Львівської політехніки, 2010)
It deals with comparison of the results of the calculations performed by frequency-symbolic method with the calculations done by MicroCAP programme and analytical solution.
Keywords: symbolic analysis of parametric circuits; linear parametric circuits; symbolic analysis